The Significant of God-Fearers for the Formation of Early Christians Identity in Acts 8-10 - Antonius Galih Arga Wiwin Aryanto (Jurnal Jaffray, 2022)
This article attempts to analyze the important role of God-fearers in informing the early Christian identity. Luke and Acts use an ethnic-reasoning to define the Christian community. Luke and Acts uses the words gentiles, unbeliever and other ethnic groups, such as Romans and Greeks, to describe outsiders. When outsiders join the Christian community, they need a new identity that contrasts with their former. This study employs ethnicity theory to understand how people from different groups accept each other while negotiating their differences, such as their cultures, beliefs, and social relationships. The conversion of the Ethiopian eunuch and Cornelius in Acts 8-10 demonstrates how the early Christians began to develop a fluid identity. Meaning some exceptions may be allowed for Gentiles to retain their practices and customs while at the same time becoming a member of the Christian community. In this new group, God-fearers find a sense of solidarity and belonging as they enter into a table fellowship in the name of Jesus Christ, showing the uniqueness of the Christian identity.